1988
DOI: 10.1161/01.res.63.4.758
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microscopy of the cerebral microcirculation using neonatal allografts in hamsters.

Abstract: Studies were performed to characterize the morphology and vascular reactivity of the allografted cerebral microcirculation. Cerebral cortical tissue was allografted into the cheek pouch of the hamster so that cerebral parenchymal vessels could be studied. The vascular morphology was characterized by a large number of looping vessels. The ultrastructural examination indicated viable cerebral tissue containing typical vessels, that is, "tight" junctions, not like those of the cheek pouch. Also, the microvasculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…low PRA associated with low renin hypertension and increased cardiovascular mortality in humans (68), often goes unnoticed. In the present study, the role of ANG II in maintaining vascular function and preventing oxidant stress in the terminal microcirculation was directly tested for the first time in a novel experimental model that is also suitable for investigation of microvascular function with implanted chambers and in allografts of multiple parenchymal tissues (8, 21, 32, 33). …”
Section: Discussionmentioning
confidence: 99%
“…low PRA associated with low renin hypertension and increased cardiovascular mortality in humans (68), often goes unnoticed. In the present study, the role of ANG II in maintaining vascular function and preventing oxidant stress in the terminal microcirculation was directly tested for the first time in a novel experimental model that is also suitable for investigation of microvascular function with implanted chambers and in allografts of multiple parenchymal tissues (8, 21, 32, 33). …”
Section: Discussionmentioning
confidence: 99%
“…Some reports indicate that regionally infused or topically applied AII results in generalized or local cerebral vasoconstriction in rabbits (Reynier-Rebuffel et al, 1983), hamsters (Joyner et al, 1988), and cats (Mayhan et al, 1988;Wei et al, 1978). Conversely, others reported that AII elicits moderate pial vasodilation in the newborn pig (Meng and Busija, 1993), rabbit (Haberl et al, 1991), and rat (Haberl et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first in vivo study determining both the time needed for BBB leakage and the quantitative severity of the permeability disturbances of the brain microvasculature during experimentally induced meningeal bacterial infections in newborns. The suitability of pial-arachnoid vessels for the study of BBB function has previously been demonstrated (15,16,20). The affected vessels with increased NaF permeability are the postcapillary venules, which are the most vulnerable vascular structures with regard to permeability within the CNS and which also behaved similarly to other noxa, such as hypertension, acidosis, and hypoxemia, and to challenge with bradykinin and histamine (14, 15, 2 1).…”
Section: Discussionmentioning
confidence: 97%
“…The permeability of the BBB can also be followed intravitally by a fluorescence photomacroscope (15)(16)(17). The BBB is tight for intravascular tracers physiologically, but certain injuries induce a BBB leakage.…”
mentioning
confidence: 99%